Implementasi Kesiapsiagaan Bencana Berbasis Masyarakat dan Penanganan Kedaruratan Medis di Lingkungan Tembalang Semarang - Resti Ariani; Bajeng Nurul W; Mugiyanto (Jurnal Mitra Pengabdian Farmasi, 2022)
The Semarang City continues make improvements to become a safe city. However, several natural disasters such as floods, tidal waves, and landslides are still an annual problem, especially during the rainy season. An alert and alert community needs to be nurtured and provided with sufficient education to take an active role in their environment. The service program in collaboration with PMI Semarang City is expected to be able to train the capabilities of the community who are prepared for disasters, as well as to form an alert character in dealing with medical emergencies. The method used in this service is in the form of training and knowledge sharing followed by question and answer. The training activity with material on Basic Life Support was attended by 30 participants consisting of RT representatives and community youth. Not only presentation of the material but also initial practical training such as Cardiopulmonary Resuscitation (CPR). At the end of the training, an evaluation of the material that has been delivered and how the level of understanding of the participants after attending the training is carried out. With the training, the people of Tembalang become more confident after carrying out the training, because they get new experience and knowledge that can be applied when a disaster occurs anytime.